Summer of '42 [videorecording (DVD)] - O'Neill, Jennifer, 1948-; Grimes, Gary, 1955-; Houser, Jerry, 1952- (Archive collection., 2014)
Coming-of-age tale about a young boy who falls for a woman seven years his senior.